A system for automatic animation of piano performances1. (21st September 2012) - Zhu, Yuanfeng; Ramakrishnan, Ajay Sundar; Hamann, Bernd; Neff, Michael
ABSTRACT: Playing the piano requires one to precisely position one's hand in order to strike particular combinations of keys at specific moments in time. This paper presents the first system for automatically generating three‐dimensional animations of piano performance, given an input midi music file. A graph theory‐based motion planning method is used to decide which set of fingers should strike the piano keys for each chord. As the progression of the music is anticipated, the positions of unused fingers are calculated to make possible efficient fingering of future notes. Initial key poses of the hands, including those for complex piano techniques such as crossovers and arpeggio, are determined on the basis of the finger positions and piano theory. An optimization method is used to refine these poses, producing a natural and minimal energy pose sequence. Motion transitions between poses are generated using a combination of sampled piano playing motion and music features, allowing the system to support different playing styles. Our approach is validated through direct comparison with actual piano playing and simulation of a complete music piece requiring various playing skills. Extensions of our system are discussed. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : This paper presents the first system for automatically generating three‐dimensional animations of piano performance, given an input midi music file. A graph theory‐based motion planning method is used to decide which set of fingers should strike the piano keys for each chord. As the progression of the music is anticipated, the positions of unused fingers are calculated to make possible efficient fingering of future notes. The system supports automatically generating animation for different complex piano techniques such as finger crossovers and arpeggio.